(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The implementation of long-termed Latvia’s development envisages the bio-fuel producing. It has been stated: the bio-fuel producing must use, in the first place, the agricultural resources grown within Latvia's territory. Among the main bio-fuel producing resources ranks rapeseed, and in Latvia developed industrial rapeseed producing connected with the concentration of agricultural resources, and the regional specialization. Especially actual is the research of the regional conditions and the impact of the concentration of production resources on the productivity of rape sowings. Our research showed that the most important rapeseed producers are the big enterprises concentrating the three fourths of the total rape sowings. One fifth of the total rapeseed sowings take medium-make farms, nevertheless the specific weight of the total rapeseed yield within this group is for one third lower than within the big enterprise group. Very few smaller farms grow rape, and small-scale farms don't grow it at all. Rapeseed productivity remarkably differs form one region to the other, and is determined not by natural factors (soil, climate etc.) alone, but, to a great extent, by the resources (manure, plant protection means) used per one territory unit as well.